Optimalisasi Pengelolaan Destinasi Wisata di Desa Bongkasa Melalui Perbaikan Praktik Community Based Tourism - I Putu David Adi Saputra; Kadek Feni Aryati (Journal of Innovative and Creativity, 2025)
Bongkasa Village, with its abundant natural and cultural potential, holds great opportunities to develop as an attractive tourist destination. Its natural beauty, ranging from green terraced rice fields to stunning mountain views, offers captivating visual appeal. The richness of local culture, such as dance, traditional music, and other local wisdom, is also a valuable asset that can be promoted. However, this potential has not been optimally explored. The management of tourist destinations in Bongkasa Village still faces various challenges, including a lack of local community participation in decision-making and management processes, inadequate infrastructure, and a lack of effective promotion and marketing. As a result, the economic benefits from the tourism sector have not been fully felt by the community, and the sustainability of the tourist destination is threatened. This condition indicates a gap between the existing potential and the reality of management that is still not optimal. Therefore, a more integrated and sustainable approach is needed to optimize the tourism potential of Bongkasa Village.